A behavioural intervention for young adults with dental caries, using acceptance and commitment therapy (ACT): treatment manual and case illustration - Werner, Helene (BMC Oral Health, 2020)
BACKGROUND: There is a need for effective behavioural interventions in dentistry. This paper presents an innovative behavioural intervention for young adults with dental caries, in an interdisciplinary collaboration between dental personnel and licensed psychologist in general dental care. The intervention has been evaluated in an RCT, with positive effects on oral health behaviour. METHOD: The intervention, Acceptance and Commitment Therapy (ACT), a recent form of cognitive behaviour therapy (CBT), was adapted to young adult patients (18–25 years of age) with high dental caries activity. RESULTS: The intervention included two individual sessions, provided by a clinical psychologist at general dental clinics. The rationale for selecting ACT as the theory base is presented, together with the treatment manual and a case illustration. CONCLUSIONS: ACT may be a promising alternative for behavioural interventions in dentistry for patients with oral diseases, specifically dental caries. Interprofessional collaboration between psychologists and dental personnel opens up for new possibilities to help and treat patients with various health issues in public dental care. TRIAL REGISTRATION: TRN ISRCTN15009620www.isrctn.com, retrospectively registered 14/03/2018.